2019
DOI: 10.1097/mcg.0000000000001183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Domperidone Use on QT Interval

Abstract: Goals: The goal of this study was to determine the effect and safety of domperidone on QTc interval at the commonly prescribed doses of 30 to 80 mg daily. Background: Domperidone is a dopamine receptor antagonist used for the treatment of gastroparesis. However, it has been associated with QT prolongation, ventricular arrhythmias, and sudden cardiac death. Study: This study analyzed patients prescribed dompe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 28 publications
0
26
0
1
Order By: Relevance
“…However, of late, given that several case reports and retrospective studies have reported an association between domperidone and severe VA, its use has been strictly restricted. Although some meta-analyses indicate that domperidone may not be associated with the risk of overall cardiovascular (CV) events and QT prolongation [15][16][17] , many clinicians hesitate to prescribe it to their patients. Thus, it is essential to conduct welldesigned studies to clarify the association between domperidone and severe VA. We conducted a self-controlled case series based on a large population cohort, which could enable the adjustment of all fixed time-independent confounders during the observation period.…”
Section: Discussionmentioning
confidence: 99%
“…However, of late, given that several case reports and retrospective studies have reported an association between domperidone and severe VA, its use has been strictly restricted. Although some meta-analyses indicate that domperidone may not be associated with the risk of overall cardiovascular (CV) events and QT prolongation [15][16][17] , many clinicians hesitate to prescribe it to their patients. Thus, it is essential to conduct welldesigned studies to clarify the association between domperidone and severe VA. We conducted a self-controlled case series based on a large population cohort, which could enable the adjustment of all fixed time-independent confounders during the observation period.…”
Section: Discussionmentioning
confidence: 99%
“…However, for patients with an underlying QT susceptibility, caution should be used. 192 Other agents with a prokinetic effect, such as acotiamide, are still under investigation and have not yet been proven effective. Evidence is limited because early studies had poor enrollment and remain incomplete.…”
Section: What Is the Role For Gastrointestinal Prokinetics In Gerd?mentioning
confidence: 99%
“…Despite the well‐known cardiac risk of domperidone, studies of real‐life use reported a very limited QT effect at low daily doses. However, for patients with an underlying QT susceptibility, caution should be used 192 …”
Section: What Is the Role For Gastrointestinal Prokinetics In Gerd?mentioning
confidence: 99%
“…26 Prospective clinical trials have not found similar effects. 20,22,27,28 Routine follow up with regular electrocardiogram is recommended. 22 Rotation from domperidone to another prokinetic agent has been suggested if a corrected QT interval of greater than 470 ms in males and 450 ms in females has been demonstrated.…”
Section: Domperidonementioning
confidence: 99%